The Role of Engineers in Advancing Sustainable Development Goal 9 in Underdeveloped Communities through Leveraging Fourth Industrial Revolution Technologies - Innocent, Ncube (INTI International University, 2024)
In underdeveloped communities, achieving Sustainable Development Goal 9 (SDG9) poses significant challenges. Underdeveloped communities lack essential services such as water purification, electricity, sanitation, health facilities and many more. Inclusivity in development stands out as one of the key drivers of SDG9. It is then quite unfortunate that underdeveloped communities have been excluded in almost all aspects of development and advancement. However gloomy the situation might look, most of the challenges faced by underdeveloped communities can be overcome if engineers are to leverage Fourth Industrial Revolution (4IR) technologies in coming up with innovative solutions for sustainable development. In 4IR technologies lie a lot of opportunities to change lives in underdeveloped communities thereby contributing significantly to the attainment of SDG9 by the year 2030. The integration of 4IR technologies such as Artificial Intelligence (AI), Internet of Things (IoT), and Renewable Energy solutions offer engineers the tools to address complex challenges and create more efficient, inclusive, and sustainable infrastructure systems. This paper explored academic literature, policy documents, and reports from reputable sources such as the United Nations (UN), and relevant engineering journal articles. Findings underscore the pivotal role that engineers should play in leveraging 4IR technologies in order to advance SDG9 through the upliftment of underdeveloped communities. A case in point where engineers have leveraged 4IR technologies in order to improve the livelihoods of the backward communities is the use of mobile money platforms in place of brick and mortar banks. Examples are, Ecocash in Zimbabwe, and Mpesa in Kenya Africa. These platforms have enabled people in underdeveloped communities to access banking facilities through their mobile phones. These banking platforms do not rely on brick and mortar facilities. They are solely based on 4IR technologies.